Analisis Penggunaan Clickbait pada Judul Berita Media Online Tribun Padang - Putri, Maisa; Eriend, Dion (CV. ITTC INDONESIA, 2024)
The purpose of the study was to determine the use of clickbait in news titles in Tribun Padang's online media without violating the journalistic code of ethics but being able to attract audiences to read the news presented by Tribun Padang's online media. The data is in the form of title sentences that publish certain criteria that are appropriate to the reasearch problem. This reasearch uses mass communication theory. The research method uses descriptive qualitative research with a case study type of research. Data was collected by interviewing sources. Data analysis uses collection, data reduction, data presentation, verification and drawing conclusions. The results of this research show that in general the use of clickbait titles is wideley uses on the subjects of celebrities, lifestyle, entertainment, health and others. The use of clickbait provides benefits to the media throughtthe number of visitor or reader traffic. The reader’s response is positive because it matches the reader’s expectations when clicking on the news title that uses the clickbait. The main purpose of using clickbait titles is to increase reader visits.